ANALISIS POTENSI & KEBIJAKAN AKUNTANSI PEMUNGUTAN PAJAK HOTEL DALAM UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KOTA PONTIANAK - B41110055, Irsalina B41110055 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
Taxes derived from hotels are a source of local revenues in Pontianak City. The targeting of hotel tax which has yet to be realistic is one of the factors causing the revenue to be below target as it should be based on the potential rather than on estimation, so the realization of revenue by a ratio of exceeding 100% is not optimal. Accordingly, in this paper intends to calculate hotel tax potential, the level of effectiveness: a tax effort and tax capacity, as well as knowing how the tax receivable accounting policies in Pontianak. The method used in this study was a descriptive method, the Tax and Revenue Office (Dispenda) of Pontianak City as the object of research. The amount of hotel tax in year t was obtained by multiplying the tax rate with the overall turnover of the hotel. The level of effectiveness was estimated by comparing between the received tax revenue and targeted as well as the potential revenues so as to obtain the ratio of tax capacity and tax effort. The policies on receivables accounting were presented clearly and in detail in accordance with the applicable rules at the Tax and Revenue Office (Dispenda) of Pontianak City. The result of the calculation showed that the amount of the potential hotel tax in Pontianak City in 2014 reached IDR 35.914.220.221 with the level of effectiveness based on tax capacity reaching 104.21% a year, but the level of effectiveness based on tax effort was 43.59% so it could not increase hotel tax revenues in Pontianak. The policies on receivables accounting on hotel tax in Pontianak were adjusted to SPTPD and SSPD at each hotel. Bad debt was recorded through the direct method and allowance method. . Keywords : Potential, Effectiveness, Capacity, Receivables Accounting Policy